Virtual machine placement algorithm based on cuckoo search - Donghan JIANG; Haitao LIN (Dianxin kexue)
A cuckoo search algorithm was introduced for virtual machine placement.Firstly,the virtual machine placement program was mapped to the nest,and according to the level,the fitness would be divided into top and bottom nest.Secondly,the bottom nest and the top nest were disturbed by the disturbance function.Finally,by selecting,iterations got the best placement scheme.The algorithm was used for physical integration of cloud data centers,minimizing the number of physical machines placed.The algorithm is simulated by Cloudsim and the results show that the proposed method not only avoids the local optimum,but also has higher performance advantages than the reordered grouping genetic algorithm,the group genetic algorithm,the improved least load algorithm and the improved first fit decrease algorithm.